2021
DOI: 10.1155/2021/9911352
|View full text |Cite
|
Sign up to set email alerts
|

Different Concentrations of Ropivacaine under Ultrasound Guidance on Quadratus Lumbar Muscle Nerve Block in Elderly Patients with Hip Replacement

Abstract: Objective. To compare the effect of ropivacaine in different concentrations under ultrasound guidance on lumbar muscle nerve blocking in elderly patients undergoing hip replacement surgery. Methods. 60 elderly patients underwent hip replacement in our hospital over a period of April to December of 2019 were equally randomized into control and observation groups, with 30 each. Patients in the control group and observation group received 0.5% and 0.25% ropivacaine to block psoas muscle nerve, respectively. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our ndings are consistent with previously published reports. Yi Han [19] found that there was no marked difference in visual analogue scores with different concentrations of ropivacaine to conduct nerve block in elderly patients with hip replacement surgery. With a xed low-dose ropivacaine with different volumes and concentrations on interscalene brachial plexus blocks, Wenwen Zhai [20] also found that there were no intergroup differences in terms of the block success rate and postoperative analgesia but a faster onset of complete sensory and motor blockade for the higher concentration groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings are consistent with previously published reports. Yi Han [19] found that there was no marked difference in visual analogue scores with different concentrations of ropivacaine to conduct nerve block in elderly patients with hip replacement surgery. With a xed low-dose ropivacaine with different volumes and concentrations on interscalene brachial plexus blocks, Wenwen Zhai [20] also found that there were no intergroup differences in terms of the block success rate and postoperative analgesia but a faster onset of complete sensory and motor blockade for the higher concentration groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 12 ] also compared low-concentration ropivacaine and high-concentration ropivacaine in transverse abdominis plain blocks in pediatric open inguinal hernia repair. Han et al [ 13 ] and Tian et al [ 14 ] reported the analgesic effects of different ropivacaine concentrations in patients undergoing hip replacement and laparotomy. Previous studies reported that 0.75% ropivacaine was within the safety limits.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the current was adjusted to 0.5 mA and the needle was slowly inserted. When contraction of calf muscles was induced and back-pumping indicated a lack of gas or blood, 20 ml 0.3% ropivacaine was injected [ 11 , 12 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%